Discurso, raça e memória: uma reflexão sobre o racismo no Brasil - Santos, Lavoisier Almeida dos (2023)
The present work analyzes the socio-historical affiliations of discourses about blackness in the social formation of the Brazilian people. The study was based on Pêcheux's Discourse Analysis anchored in historical-dialectical materialism. Throughout the text, the relationship between discourse, race and discursive memory in the understanding of racism in Brazil is analyzed. To this end, materials that convey everyday, literary and, supposedly scientific, discourses about blackness are used. As a result, it is demonstrated that some of these discourses summarize the discursive memory of the body of black subjects as a free territory for any and all types of aggression triggered by white subjects. Other discourses seek to ban blackness in a more veiled way, either by defending its necessary whitening, or by dissolving its culture and uniqueness in the vague concept of miscegenation. Finally, we conclude by stating that the relationship between discourse and race in Brazil is ideologically inscribed in a social and historical position that (re)produces feelings of inferiority and/or denial of blackness as a Brazilian national identity.